SISTEM PENDUKUNG KEPUTUSAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING UNTUK PEMILIHAN KARYAWAN BARU DAN PROMOSI JABATAN (Studi Kasus : PT. Putra Sumber Utama Timber) - Ezrifal Sany; Susi Susanti (JURNAL AKADEMIKA)
Employees are one of human resources is essential to support in advancing the company and quite influential in the profits earned by the company. Decision support system sel ection and promotion of new employees on PT. Putra Sumber Utama Timber using Simple Additive weighting method is one of the efforts to be made in the process of assessing prospective new hires and employees who will be promoted in the election office in order to more accurately and in accordance with the criteria expected. Criteria used in the selection of a new employee: education, height, health, strength, experience, appearance and ethical attitude while for the criteria in the selection of his employees were promoted: education, employment, discipline, quality of work , honesty, personality, teamwork, tenacity , communicative and responsibility. Data collected by the methods of research interviews, direct observation and literature. Needs input required is applicant data, employee data, the data positions, the data value of the weight or importance of each criterion. If the needs of the process in the form of alternative data is done through the initial selection process, the decision matrix computation, calculation of the normalization matrix, calculating the value of the vector of each alternative. The output of the data reporting needs of applicants, employee data, the data positions, reports the results of the vector applicants and report the results of a vector value employees who value vector has been ordered from the highest to the smallest value vector. This system is built using a programming language Delphi 7.0 with SQLyog database. This system is interactive making it easier for users, especially the HRD (Human Resources Of Development) to process the data and in making better decisions and to minimize errors in the assessment of prospective new employees and employees who will be promoted post.